Standardization of CT Depiction of Cochlear Implant Insertion Depth - Colby, C.C.; Todd, N.W.; Harnsberger, H.R.; Hudgins, P.A. (American Journal of Neuroradiology, 2015)
BACKGROUND AND PURPOSE: Imaging a cochlear implant with CT is challenging because of implant-induced artifacts, anatomic cochlear variations, and lack of standard terminology for cochlear anatomy. The purposes of this project were to determine whether the cochlear implant tip was more accurately located on oblique CT reformations than on standard images, to review radiology reports for accurate cochlear implant locations, and to assess agreement between an implant surgeon and neuroradiologist by using standardized cochlear anatomy terminology for cochlear implant depth. MATERIALS AND METHODS: In this retrospective study, a neuroradiologist and an implant surgeon independently viewed temporal bone CT images of 36 ears with cochlear implants. Direct axial images, standard coronal reformations, and oblique reformations parallel to the cochlea were compared to determine implant tip location, which was described by using a proposed standardized quadrant terminology. Implant locations were compared with the initial formal report generated by the original interpreting neuroradiologist. RESULTS: Thirty-six temporal bones with cochlear implants underwent CT interpretation for implant location. Interobserver agreement was similar when comparing cochlear implant tip location by using a quadrant nomenclature on axial and coronal images and on oblique reformations. Clinical radiology reports all were imprecise and ambiguous in describing the location of the cochlear implant tip. CONCLUSIONS: Accurate determination of insertion depth of the cochlear implant array can be determined by assessment of the implant tip on axial, coronal, and oblique CT images, but description of the tip location can be inaccurate due to lack of standardized terminology. We propose using a standardized terminology to communicate tip location by using the round window as the zero reference and quadrant numbering to describe cochlear turns. This results in improvement in radiology report accuracy and consistency regarding the cochlear implant insertion depth. CIcochlear implant